2022
DOI: 10.1038/s42003-022-03460-3
|View full text |Cite
|
Sign up to set email alerts
|

Coral fluorescence: a prey-lure in deep habitats

Abstract: Fluorescence is highly prevalent in reef-building corals, nevertheless its biological role is still under ongoing debate. This feature of corals was previously suggested to primarily screen harmful radiation or facilitate coral photosynthesis. In mesophotic coral ecosystems (MCEs; 30-150 m depth) corals experience a limited, blue-shifted light environment. Consequently, in contrast to their shallow conspecifics, they might not be able to rely on photosynthates from their photosymbionts as their main energy sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…While GFP-like proteins are likely to have additional functions for the coral holobiont ( Aihara et al, 2019 ; Ben-Zvi et al, 2022 ; Yamashita et al, 2021 ), optimisation of the symbiont light environment is arguably one of their primary roles. The effects of GFP-like proteins on the light environment experienced by coral symbionts are not simply dependent on the spectral properties of the isolated protein; rather, they are a product of the environmental and physiological regulation of the protein within its three-dimensional optical context.…”
Section: Introductionmentioning
confidence: 99%
“…While GFP-like proteins are likely to have additional functions for the coral holobiont ( Aihara et al, 2019 ; Ben-Zvi et al, 2022 ; Yamashita et al, 2021 ), optimisation of the symbiont light environment is arguably one of their primary roles. The effects of GFP-like proteins on the light environment experienced by coral symbionts are not simply dependent on the spectral properties of the isolated protein; rather, they are a product of the environmental and physiological regulation of the protein within its three-dimensional optical context.…”
Section: Introductionmentioning
confidence: 99%
“…We found UV induced fluorescence emissions primarily from the peristomes of various Nepenthes species/hybrids (Kurup et al 2013). Recent studies have demonstrated fluorescence as a visual signal in floral reproductive structures (Mori et al 2018), amphibians (frogs), marine organisms, segmented worms, reptiles and other organisms (Taboada et al 2017; Mori et al 2018; Kohler et al 2019; Ben-Zvi et al 2022). In another recent study, we demonstrated Nepenthes pitchers as CO2-encriched cavities, and open pitchers continually emit CO2 attracting preys towards them (Baby et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similar fluorescence emissions from reproductive structures (anther, pollen) were proved to be visual cues attracting pollinators to flowers (Baby et al 2013; Mori et al 2018). Fluorescence also functions as signals in various amphibians (frogs) in terrestrial environments, marine organisms, segmented worms, reptiles and other organisms (Taboada et al 2017; Mori et al 2018; Kohler et al 2019; Ben-Zvi et al 2022). In Nepenthes , the peristome is a wettable surface with distinct microstructures (Bohn and Federle, 2004; Chen et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They have also been proposed to amplify light scattering and increase the temperature within coral tissue (Lyndby et al, 2016). It also has been suggested that animal CPs could help corals attract symbionts (Aihara et al, 2019) and prey such as plankton (Ben-Zvi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%